A low albumin to globulin ratio with a high serum globulin level is a prognostic marker for poor survival in cervical cancer patients treated with radiation based therapy. Issue 1 (January 2019) - Yoshino, Yasunori; Taguchi, Ayumi; Shimizuguchi, Takuya; Nakajima, Yujiro; Takao, Maki; Kashiyama, Tomoko; Furusawa, Akiko; Kino, Nao; Yasugi, Toshiharu
Abstract : Objective: We investigated whether the pretreatment albumin to globulin ratio, serum albumin level, and serum globulin level can be used to predict survival among cervical cancer patients treated with radiation based therapy and assessed globulin fractions. Methods: We retrospectively enrolled 128 patients with cervical cancer treated with radiation based therapy at our institution between 2010 and 2015. The associations of the pretreatment albumin to globulin ratio, and serum albumin and globulin levels with overall survival were assessed. Additionally, the associations of the globulin fractions with the serum globulin levels and overall survival were evaluated. Results: Median follow-up duration was 30 months (IQR 16–44 months). A low albumin to globulin ratio (< 1.53) was found to be an independent prognostic factor for overall survival (HR= 3.07; 95% CI, 1.03 to 13.3; P=0.044). On evaluating serum globulin and albumin separately, a high serum globulin level was significantly associated with overall survival (cut-off value 2.9 g/dL; HR=3.74; 95% CI 1.08 to 23.6; P=0.036) whereas a low serum albumin level was not associated with overall survival (cut-off value 3.6 g/dL; HR=1.77; 95% CI 0.57 to 4.54; P=0.29). Electrophoresis data of the serum proteins revealed that the γ-globulin fraction was most strongly correlated with the globulin levels (P<0.001). Furthermore, a high γ-globulin level (≥1.28 g/dL) was significantly associated with poor overall survival (log rank test, P=0.034). Conclusions: A pretreatment low albumin to globulin ratio, which might be attributable to a high serum globulin level, can be used to predict poor prognosis in cervical cancer patients treated with radiation based therapy.